2016
DOI: 10.1080/00071668.2016.1154504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season on the reproductive organs and steroid hormone profiles in guinea hens (Numida meleagris)

Abstract: The study documented gross anatomical and histological differences in the reproductive organs of 28 breeding and non-breeding female guinea fowls. Peripheral progesterone and 17β-oestradiol concentrations were also compared in breeding and non-breeding hens. In non-breeding females, all ovarian and oviducal gross anatomical features had significantly regressed. Histologically, some of the changes in a regressing oviduct include systematic changes in height and size of all epithelial cells in all regions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…For instance, while Furr (1969) reported higher values in laying birds about 12–14 h after ovulation, Etches (1990) noted that the peak occurs 6 to 4 h before ovulation. Abdul-Rahman et al. (2016a) also reported a concentration of 5.29 ng/ml about 1–2 h prior to lay and 0.57 ng/ml post-lay in the guinea fowl.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…For instance, while Furr (1969) reported higher values in laying birds about 12–14 h after ovulation, Etches (1990) noted that the peak occurs 6 to 4 h before ovulation. Abdul-Rahman et al. (2016a) also reported a concentration of 5.29 ng/ml about 1–2 h prior to lay and 0.57 ng/ml post-lay in the guinea fowl.…”
Section: Discussionmentioning
confidence: 88%
“…As with testosterone, 17β-oestradiol assay had also been previously validated for guinea fowl ( Abdul-Rahman et al., 2016a ). Using the Oestradiol Maia kit (RADIM diagnostics, USA), all samples were evaluated in one assay, and intraassay CV was 9.8%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where demand is not met as occurs during the rainy season, the wholesalers travel far, assembling birds from the few farmers willing to sell to meet the demand of their clients [29]. The seasonal availability of products may be related to the seasonal breeding habit of these birds [30][31], as farmers are usually unwilling to sell their birds during the breeding season, which occurs in the rainy season. X2 (5%) = 44.7, df = 2, p = 0.064…”
Section: Resultsmentioning
confidence: 99%
“…ADCYAP1R1 was the receptor gene of pituitary adenylate cyclase-activating polypeptide type 1 receptor ( PAC1 ), Mercer et al found that SNP rs2267735 within the ADCYAP1R1 located within a predicted estrogen response element, which regulates gene transcription when bound to estradiol (E 2 ) activated estrogen receptor alpha (ER α ) ( Mercer et al, 2016 ). However, numerous pieces of evidence have confirmed that the concentration of E 2 was strongly affected by seasonal or photoperiodic change ( Lai et al, 2012 ; Abdul-Rahman et al, 2016 ; Carr et al, 2003 ). PER1 is one of the typical clock genes, whose expression is significantly correlated with circadian rhythm ( Albrecht & Eichele, 2003 ; Messager et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%